Cellularity, characteristics of hematopoietic parameters and prognosis in myelodysplastic syndromes. (15th May 2015) - Schemenau, Jennifer; Baldus, Stephan; Anlauf, Martin; Reinecke, Petra; Braunstein, Stefan; Blum, Sabine; Nachtkamp, Kathrin; Neukirchen, Judith; Strup, Corinna; Aul, Carlo; Haas, Rainer; Gattermann, Norbert; et al.
Abstract Background Myelodysplastic syndromes (MDS) present with a normo‐ or hyperplastic bone marrow in most cases. We aimed at a characterization of patients with different types of cellularity. Methods We assessed marrow cellularity both by histology and cytology in 1270 patients and analyzed hematologic, cytogenetic, and prognostic parameters accordingly. Results The concordance of the assessment of cellularity differed dramatically between histology and cytology as only 36.5% were described as hypocellular by both methods (P < 0.0005) (hypocellular 16.4%, normocellular 23.3%, hypercellular 60.3%). There were no major differences with regard to hematopoietic insufficiency. The presence of fibrosis was associated to hypercellular bone marrow. Median survival differed from 38 months in hypocellular, 42 months in normocellular, and 25 months in hypercellular MDS (P < 0.0005). AML progression rates were 33% for hypercellular MDS after 2 yr, whereas hypo‐ and normocellular had a progression rate of 19% after 2 yr (P = 0.018). IPSS and IPSS‐R were able to identify different risk groups within all three cellularity groups. Conclusion Based on our data, hypocellular patients obviously do not present as a separate entity, as there were no striking differences with regard to cytogenetics and WHO types. Assessment of cellularity should be performed by histopathology.